Discursos midiáticos sobre as políticas públicas contemporâneas para o ensino de Língua Espanhola no Brasil - Nascimento, Thaíse Cristina Silva do (2019)
This study aims to present a discursive analysis of Internet publications about contemporary public policies for the provision of Spanish language in Brazilian regular education, since media conditions reproduce and crystallize the discourses in operation. The work uses as a theoretical-methodological approach the Discourse Analysis, with the purpose of understanding the way the political gestures were built by the obligatoriness and facultativity in the following historical outline: after the publication of Law No. 11.161 / 2005 and PM 746/2016, Law No. 13.415 / 2017. As a theoretical framework, the research brought contributions from authors such as: Louis Althusser (1998), Michel Pêcheux (1997; 1999; 2010), Jacqueline Authier-Revuz (1990), Eni P. Orlandi (1996b, 1998, 2007, 2015) , Alice Krieg-Panque (2010), Maria do Rosário FV Gregolin (2007), among other authors who developed research on discourse and media. In the constitution of the empirical corpus, the method considered the headlines found in different types of sites, meaning as "great press", in addition to those built as a journalism on the fringes of it. In relation to the obtained results, about the compulsory offer of the Spanish language teaching (2005), the analysis of the discursive forms and formulas verifies that the constitution of the subject occurs from the intersection of discourses of the new, the legal-political, the scholar and pedagogical, marketing and labor, quantitative and bureaucratic. Yet the analytical gestures woven from the publications about the facultative offer (2016/2017), presents the confrontation of antagonistic political positions, regulating and categorizing the teaching of Spanish through an erasure. By joining the ideology of “right” politics, the subject is constituted by the discourse of the new positive, openness and democracy. On the other hand, the subject, affiliated to the ideology of the "left", is constituted by a discourse of personal, undemocratic and marketing, in the circulation of negative meanings for the facultativity of language offer.